"I have been refused to be treated by three dentists": Barriers to patient care. (1st May 2020) - Abed, Hassan; Abuljadayel, Jameel
Abstract: Background: Factor X deficiency (known as; Stuart‐Prower factor deficiency or F10 deficiency) is a rare inherited bleeding disorder. It affects one per 1 million individuals worldwide. Patients with inherited bleeding disorder reported difficulty in accessing primary dental care either due to their medical diseases or their related barriers. Aim: This article aims to identify barriers to oral health as perceived by the patient with factor X deficiency who had been refused treatment by three dentists. A further aim is to provide dentists with the knowledge required to manage patients diagnosed with factor X deficiency. Methods and Case Report: A 30‐year‐old male with the inherited, severe factor X deficiency (<1%) was asked to complete a survey which includes 22 semistructured, validated questions to assess his perceived barriers to dental services. Dental examination revealed that the patient required having nonsurgical periodontal therapy under local anesthesia. The treatment plan was discussed with the patient and his hematologist. The patient's hematologist advised performing dental treatment shortly (ie, 1‐2 h) after hematological cover with a prothrombin complex concentrate (1000 U; Octoplex ® ) via intravenous infusion. The hematologist also prescribed tranexamic acid mouthwash (250 mg in 5 mL) and the patient was instructed to rinse his mouth for 3‐5 min with 500 μg (10 mL) in case of bleeding following treatment. Findings: The patient reported several barriers to dental services such as high anxiety levels regarding oral bleeding, difficulty in finding a suitable dental clinic, high cost of dental treatment, and the need for hematological cover prior to dental treatment. Conclusions: The proper communication between dentist and hematologist was a vital step to render safe and effective dental care and to reduce the patient's anxiety toward the dentist.